ANALYSIS OF ONLINE LEARNING MOTIVATION IN STUDENTS XI SMA NEGERI 1 JENEPONTO - Syarbini, Nuzul; Andi Maulana; Wiwin Pramita Arif (Journal of Islam and Science, 2022)
The purpose of this study was to determine the motivation for online learning and to identify the factors that hinder and support the implementation of online learning in Class XI students of SMA Negeri 1 Jeneponto. The type of research used by the researcher is qualitative research. The data comes from the words or actions of the researchers' online interviews, voice recordings, and student learning documentation at SMAN 1 Jeneponto. In this case, the subjects are also Class XI students who are also part of the resource persons in this study, whose criteria are determined through purposive sampling technique. The results of the study show that for various reasons, the learning motivation of SMAN 1 Jeneponto students with online learning has decreased during the COVID-19 pandemic. In terms of inhibiting factors, one of them is that students have difficulty accessing the internet caused by network or signal disturbances when participating in online learning, while the other side is being able to reduce the spread of COVID-19.